PENGARUH MODAL INTELEKTUAL PADA KINERJA ORGANISASIONAL (Studi Pada Institusi Pendidikan Tinggi) - Fairuzzabadi . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
The study aims to examine one aspect of the resource-based view, intellectual capital, and it’s three components – human, structural, and relational capital. We hypothesize that the impact of each component of intellectual capital on organizational performance in a sample of private higher education institution in Yogyakarta. The regressions results indicated the organizational performance of higher education institution well explained by each component of intellectualcapital. The empirical findings and the ensuing discussion will be of interest to managers and practitioners.Keyword: intellectual capital, organizational performance, higher education institution.